PENGEMBANGAN LKPD BERBASIS PROBLEM BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN LITERASI NUMERASI DAN KEMANDIRIAN BELAJAR - Dewi, Debora Sari; Fauzi , Kms. Muhammad Amin; Sutopo, Adi; Syahril (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2025)
R&D research aims develop PBL -based LKPD for increase literacy numeracy and independence Study student in accordance with criteria valid, practical, and effective teaching tools. The development model used is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The research show validity the highest on LKPD was 4.94 (valid), and the lowest on pretest - posttest questions of 4.70 (valid). Practicality increase from trial I (no need revision 23%, revision small 76.7%) to trial II (no need revision 93.3%, revision small 6.7%). Observation implementation learning show improvement from trial I (average 2.52 or 50.83%, quite good) to trial II (average 4.71 or 95.52 %, very good). Effectiveness seen from activity students and questionnaires response. Activity student increase from trial I (average 2.79 or 56.67%, quite good) to trial II (average 4.13 or 89.98 &, very good). Response students also increased from neutral (62.20%) to interested (86.02%). Ability literacy numeracy based on N-gain increase from trial I (0.34, no effective) to trial II (0.771, effective). Independence learning also increases from category Enough independent (41.3%) to very independent (87.8%).